2018
DOI: 10.1186/s12913-018-3304-6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the implementation and efficacy of a home-based strength and balance fall prevention intervention in people aged 50 years or over with vision impairment: a process evaluation protocol

Abstract: BackgroundA nested process evaluation, within a randomised controlled trial, will explore relationships between program outcomes and quality of intervention implementation of the Lifestyle-Integrated Functional Exercise Program in older people with vision impairment. The Lifestyle-Integrated Functional Exercise Program is a home-based strength and balance program that has been shown to reduce falls in high risk populations. A pilot study showed positive trends in improvements in physical function in older peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…[5,7,8] The postural control variables may be reduced when sensory systems are altered. [9,10] A common method of studying standing balance is to record body segment motion equilibrium, which is unstable, and small fluctuations are seen in balance measurements that reflect continuous and intermittent muscle activity. [11] Balance is defined as the maintenance of the vertical projection of the body's center of mass (COM) onto the support area formed by the feet.…”
Section: Introductionmentioning
confidence: 99%
“…[5,7,8] The postural control variables may be reduced when sensory systems are altered. [9,10] A common method of studying standing balance is to record body segment motion equilibrium, which is unstable, and small fluctuations are seen in balance measurements that reflect continuous and intermittent muscle activity. [11] Balance is defined as the maintenance of the vertical projection of the body's center of mass (COM) onto the support area formed by the feet.…”
Section: Introductionmentioning
confidence: 99%
“…This will include fidelity of delivery, number of sessions required, and associations between participants' demographic, functional, clinical and visual function characteristics with participants' receipt and enactment of programme activities. 27 The current study has the potential to inform developers of exercise programmes for the prevention of falls in older adults with vision impairment or those looking to include people with vision impairment into existing programmes. This includes eligibility criteria, particularly in terms of what age range or physical ability would suit the programme in its current form.…”
Section: Resultsmentioning
confidence: 99%
“…A good number of studies with multifaceted intervention strategies have reported significant positive effects on falls [73][74][75]. Some other studies reported no significant impact of multifaceted interventions on falls [76,77], while another study found no apparent overall effects of these interventions on falls [78]. A standard, consistent component of multiple interventions significantly associated with reducing the number of fallers and falls rate were exercise, assistive technology, environmental assessment with modifications, quality of life improvement strategies, and basic fall risk assessment.…”
Section: Therapeutic Exercises In Fall Managementmentioning
confidence: 99%